2018
DOI: 10.1002/asl.871
|View full text |Cite
|
Sign up to set email alerts
|

The influences of ocean on intensity of Typhoon Soudelor (2015) as revealed by coupled modeling

Abstract: Typhoon Soudelor (2015) moved northwestward toward Taiwan and passed several mesoscale ocean eddies over the open ocean. A high-resolution air-sea coupled model HWRF is employed to simulate Soudelor. Coupled model with low-or high-resolution ocean conditions can largely reduce the over-intensification of the typhoon from uncoupled modeling. Coupled modeling with a more realistic finer-resolution Hybrid Coordinate Ocean Model (HYCOM) analysis helps better capture the rapid weakening of the super-intense typhoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Although coupled simulations of tropical cyclones exist with a smaller horizontal grid spacing of 2–3 km, this is the first study of a tropical cyclone simulated in a global domain with no nesting and a grid spacing as low as 5 km for both the atmosphere and the ocean (Chen et al ., 2017; Li and Huang, 2019). Because horizontal diffusion parametrised in boundary‐layer schemes typically scales with the horizontal grid spacing in mesoscale models, simulated tropical cyclone intensity can increase when the horizontal grid spacing is decreased (Rotunno et al ., 2009).…”
Section: Icon Model Description and Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although coupled simulations of tropical cyclones exist with a smaller horizontal grid spacing of 2–3 km, this is the first study of a tropical cyclone simulated in a global domain with no nesting and a grid spacing as low as 5 km for both the atmosphere and the ocean (Chen et al ., 2017; Li and Huang, 2019). Because horizontal diffusion parametrised in boundary‐layer schemes typically scales with the horizontal grid spacing in mesoscale models, simulated tropical cyclone intensity can increase when the horizontal grid spacing is decreased (Rotunno et al ., 2009).…”
Section: Icon Model Description and Simulationmentioning
confidence: 99%
“…However, the process by which tropical cyclone intensity changes is far from straightforward. Recent studies using coupled models turn to Emanuel's influential paradigm to explain changes in tropical cyclone intensity due to a cold wake (Emanuel, 1989; 1995; 1997; Lee and Chen, 2014; Chen et al ., 2017; Li and Huang, 2019). However, one shortcoming of this paradigm is that, while considering boundary‐layer thermodynamics, it does not recognise the importance of atmospheric boundary‐layer dynamics to spin up (Montgomery and Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A statistical research has reported that the regions where intense TCs are observed correspond to those of active WCEs, and 70% of observed TCs over the Western North Pacific encounter the WCEs at least one time (Ma et al, 2017). Under these backgrounds, a lot of studies regarding the local influence of ocean conditions associated with the WCEs on TC intensity have been conducted for the real TCs such as Hurricane Opal (Shay et al, 2000), Hurricane Katrina (Wu et al, 2007), and Typhoon Soudelor (Li & Huang, 2019) and for the idealized TC (Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The oceanic conditions occurring directly below the tropical cyclone, both surface and sub-surface, are often forgotten or not included in the analysis. Hence model studies are required to understand the oceanic processes that happen during the passage of tropical cyclones and how energy is transferred for cyclonic intensifications (Li and Huang 2019;Tada et al 2018). Atmospheric models use the observational SST data as oceanic forcing to simulate the cyclone track and intensity.…”
Section: Introductionmentioning
confidence: 99%